Nonlinear Variable Resistor-Based FCL for Fault Ride-Through Performance Enhancement of DFIG-Based Wind Turbines. (18th June 2021) - Firouzi, Mehdi; Shafiee, Mohammadreza; Nasiri, Mojtaba
Abstract : Fault ride-through (FRT) requirement is a matter of great concern for doubly fed induction generator (DFIG-) based wind turbines (WTs). This study presents a nonlinear variable resistor- (NVR-) based bridge-type fault current limiter (BFCL) to augment the FRT performance of DFIG-based WTs. First, the BFCL operation and nonlinear control design consideration of the proposed NVR-based BFCL are presented. Then, the NVR-BFCL performance is validated through simulation in PSCAD/EMTDC software. In addition, the NVR-based BFCL performance is compared with the fixed resistor- (FR-) based BFCL for a three-phase symmetrical short circuit fault at the grid side. Simulation results reveal that the NVR-based BFCL provides a smooth and effective FRT scheme and outperforms the FR-based BFCL.